Medulloblastoma of Cerebellopontine Angle Region - Fadal Alretimi; Hesham Ben Khayal; Abdussalam Abograra Said; Lubna Azzouz; Amani Masoud (Current Overview on Disease and Health Research Vol. 7, 2023)
Cerebellopontine angle (CPA) medulloblastomas (MB) are rare lesions, with only a few cases previously reported in the literature. This chapter presents a case of CPA MB. The patient was a 36-year-old female who had developed a mass in her CPA. In this case, the preoperative radiological diagnosis was (hemangioblastoma). The patient was operated on in the neurosurgical department of Tripoli University Hospital in September 2020, using a (retrosigmoid) approach. The intraoperative findings revealed an extra-axial tumour, and the histological diagnosis in this case was classic type of MB. We conduct a literature review, address the pathological, radiological, and clinical follow-up aspects of CPA MB, and emphasise the importance of taking MB into account when making a differential diagnosis of CPA lesions.